The protagonism of technology in communication processes and the potentialization of inequalities in internet access in Brazil (Revista Internacional de Folkcomunicação, 2023)
The exception character that ruled the everyday life of the entire planet because of the Covid-19 pandemic during the year of 2020 set new coexistence parameters, one of the premises to the contagion containment being isolation and social distancing. Facing the impossibility of face to face contact, in practically every social and interpersonal relationship (family, professionally, educationally), the technologic, midia and digital solutions definietly took the main role on communication processes. This article discusses this agenda of technological acceleration from an essential counterpoint to it's implementation in our country: 18% of brazilian households do not have internet access, according to the research TIC-2021 data. This corresponds to 35,5 million people who are not connected to the global computer network and to for which the obstacle is the elevated prices that carriers charge for the service. The "real life" structural problems clearly mirror the "virtual life", increasing and inequality and reinforcing the digital exclusion of the citizens that that already live in a social disjunction process. When rescuing the actor-network theory, from Bruno Latour, that discusses about the space-network and its transformation from the relation between humans and non-humans, what is intended is to dialogue with the concept of Folkcommunication from the activist media conceptions brought by Osvaldo Trigueiro, in order to understand how this last one may be an alternative way for some kind of access to this "disconnected" mass of brazilian population.
Keywords: Media; Technology; Communication processes; Actor-network; Folkcommunication.